An evaluation of the relevance of real estate curricula in Botswana. Issue 3 (19th June 2017) - Kampamba, Johnson; Tembo, Emmanuel; Nkwae, Boipuso
Abstract : Purpose: The purpose of this paper is to establish the relevance of the real estate curricula being offered by the two universities in Botswana to industry. Design/methodology/approach: This is a cross-sectional study in which a designed questionnaire was administered to the practitioners in real estate obtained from the membership list of the Real Estate Institute of Botswana (REIB), final-year students and former graduates of the Bachelor of Land Management programme using proportionate stratified random sampling technique. This resulted into the total population of 150 elements. Students for the Bachelor of Commerce in Real Estate (BCom RE) at Ba Isago and BSc Real Estate programme at the University of Botswana were excluded from the population because they did not have graduate degrees yet; therefore the study sample was drawn from the identified population at 90 per cent confidence level with a 10 per cent margin of error. The sampling frame composed of 122 registered property valuers and managers, 14 alumni and 14 final-year students of Land Management (150). The sample size of 60 was determined at 90 per cent level of confidence with a 10 per cent margin of error. The questionnaire was administered through e-mail using a contact list from the REIB to their members. It was also e-mailed to the alumni and physically administered to the final-year students as well. A 60 per cent response rate was achieved. Findings: It was established that the three programmes offered at the two universities in their current form are relevant to the industry. The overall average scores out of 5 for these programmes were 4.14 for BSc Real Estate – UB, 4.10 for Bachelor Land Management – UB and 3.97 for BCom RE – Ba Isago University College. By using analysis of variance, the study further established that there were no significant differences between the two programmes that are offered at UB and the one at Ba Isago University College. This was established by looking at the computed F -test (0.89) and the critical F -test (2.36). Since the computed F -test was less than the critical F -test value, it was concluded that there is no significant statistical differences among the three programmes being offered in the two universities. Research limitations/implications: The major limitation in this study was the use of an e-mailed questionnaire to the property practitioners and alumni of the Land Management programme which is characterised by a low response rate. Practical implications: Since the three overall mean scores are close to and above 4.00, it means the current programmes offered at the two universities are relevant to the industry. Social implications: The research results might be useful to the society and should be used to enhance the social uplifting of society by contributing to the decisions that are made which might affect the society as a whole. Originality/value: This is the first study to be conducted in Botswana which was meant to establish if the real estate programmes offered in the two universities were relevant. It is the first study to compare and evaluate the relevance of the contents of three real estate programmes locally.